Development of Android Based Physics E-Module with Project Inside to Increase Pancasila Student Profiles - Rooseno, Yohan; Wiyanto, Wiyanto; Adhi, M. Aryono (Physics Communication, 2024)
Policy of Indonesian government through Ministry of Education and Culture in implementation of merdeka curriculum give new view to achievement character of students. It called Pancasila Students Profile and project-based learning (PjBL) as an appropriate learning model with curriculum. This makes all subjects in applied curriculum contain values Pancasila Students Profile. As science, physics can be designed to contain values Pancasila Students Profile and project-based learning by using media formed of e-modules. Based on the matter, researchers carry out related RD with use of e- modules physics with integrated of Pancasila Students Profile and PjBL. The objectives of this research are describing characteristics of e- module android-based for high school physics with project contain and its effectiveness on Pancasila Student Profiles. The method of this study is RD with the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. This study produced e-module android-based for high school physics with project-loaded. E-module has characteristics typical that existed Pancasila Students Profile and projects simulation inside. The developed e-module proved to be very useful when used, according to evaluation experts. Implementation of e-modules physics in learning can increase whole dimensions of Pancasila Students Profile namely dimensions believe, fear to God Almighty, morals noble, global diversity, independent, creative, critical thinking and cooperative. E-module proved its practicality, according to user view.